Money supply and exchange rate and their impact on the management of international reserves in Japan (2003-2015) - Hashem Jabbar Al - Husseini,; Riad Rahim Al Ameri, (Iraqi Journal for Administrative Sciences, 2024)
Changes in the money supply and exchange rate under any internal or external conditions, as planned by the monetary and financial authorities, must be accompanied by an inevitable financial and monetary implications for all variables within the Japanese economy. The most prominent of these changes are the international reserves. Japan's monetary and fiscal policies clearly and positively manage and accumulate those reserves, The latter is an effective tool in guiding the economy policy within the country in accordance with the feedback base, leading to substantial stability in the supply of money and exchange rates, which supports economic stability as a whole. The change in the supply of money has the greatest impact on the accumulation and growth of these reserves, while the floating exchange rate regime has been significantly weakened in addition to the steps taken by Japanese producers to effect the exchange rate on the management of international reserves.